The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1124/jpet.112.201061
|View full text |Cite
|
Sign up to set email alerts
|

Mending Leaky Blood Vessels: The Angiopoietin-Tie2 Pathway in Sepsis

Abstract: Sepsis is a systemic inflammatory response to infection. A common end-feature, these patients regularly suffer from is the so-called multiple organ dysfunction syndrome, an often fatal consequence of organ hypoperfusion, coagulopathy, immune dysregulation, and mitochondrial dysfunction. Microvascular dysfunction critically contributes to the morbidity and mortality of this disease. The angiopoietin (Angpt)/Tie2 system consists of the transmembrane endothelial tyrosine kinase Tie2 and its circulating ligands (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 42 publications
0
67
0
1
Order By: Relevance
“…In the context of the developing blood vessels, this may alter the expression of pro-angiogenic signaling molecules such as VEGF as well as molecules that maintain blood vessel integrity (e.g., angiopoeitin-1/2). 52 The in vivo expression of SP-A in the mouse retina after intravitreal injection of TLR-2 and TLR-4 ligands demonstrates that inflammatory pathways induced by common bacterial pathogens (e.g., LPS-mediated TLR-4 activation) led to an increase in retinal SP-A levels, Although our data are from adult mice, several studies have shown an increased risk of ROP in the face of maternal chorioamnionitis with postnatal infections and sepsis. 21,53 Our in vivo studies demonstrated that SP-A expression was more pronounced for LPS-mediated TLR-4 activation, although Pam3Cys-mediated TLR-2 activation was found to occur earlier (12 hours vs. 6 hours).…”
Section: Sp-a Up-regulation Is Mediated By Tlrs and Nfjb Pathwaymentioning
confidence: 72%
“…In the context of the developing blood vessels, this may alter the expression of pro-angiogenic signaling molecules such as VEGF as well as molecules that maintain blood vessel integrity (e.g., angiopoeitin-1/2). 52 The in vivo expression of SP-A in the mouse retina after intravitreal injection of TLR-2 and TLR-4 ligands demonstrates that inflammatory pathways induced by common bacterial pathogens (e.g., LPS-mediated TLR-4 activation) led to an increase in retinal SP-A levels, Although our data are from adult mice, several studies have shown an increased risk of ROP in the face of maternal chorioamnionitis with postnatal infections and sepsis. 21,53 Our in vivo studies demonstrated that SP-A expression was more pronounced for LPS-mediated TLR-4 activation, although Pam3Cys-mediated TLR-2 activation was found to occur earlier (12 hours vs. 6 hours).…”
Section: Sp-a Up-regulation Is Mediated By Tlrs and Nfjb Pathwaymentioning
confidence: 72%
“…Although some studies suggest a protective role of Angpt-2 in the context of infection, the majority of the literature supports the concept that Angpt-2 is deleterious in sepsis (reviewed in 55 ). Recently, Western analysis of lung homogenates from septic mice has shown that Angpt-2 siRNA-knockdown restores Tie2 phosphorylation, providing in vivo evidence that the induction of Angpt-2 in sepsis leads to Tie2 deactivation and that Angpt-2 worsens outcomes in sepsis.…”
Section: -24mentioning
confidence: 99%
“…Ang-1 and -2 are important regulators of angiogenesis, inflammation and vascular permeability [78,79]. Binding of constitutively expressed Ang-1 to Tie2 induces endothelial quiescence, integrity and barrier stabilisation.…”
Section: Improving Pulmonary Barrier Functionmentioning
confidence: 99%